Cytopathological Spectrum of Salivary Gland Lesions According to the Milan System for Reporting Salivary Gland Cytopathology: A Retrospective Study - Datta, Balmiki; Daimary, Michimi; Bordoloi, Krishangee; Thakuria, Chandrama (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC), developed in 2015, aims to standardize reporting of salivary gland cytology, enhance communication between clinicians and institutions, and ultimately improve patient care outcomes. This study aimed to determine the cytopathological spectrum of salivary gland lesions using the MSRSGC at a tertiary care hospital in northeast India. Materials and Methods: Clinical data and cytology smears of salivary gland lesions diagnosed between January 2016 and May 2021 were retrieved. All cytology smears were reviewed and reclassified into one of the six MSRSGC categories using strict criteria. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of fine-needle aspiration cytology (FNAC) for detecting malignant lesions were calculated using histopathological examination (HPE) as the gold standard. Results: A total of 57 salivary gland lesions were examined. Thirty-one (54.38%) were male and 26 (45.6%) were female, with a median age of 34 years (range 6-70 years). Statistical analysis revealed a sensitivity of 75%, specificity of 100%, positive predictive value of 100%, negative predictive value of 95%, and a diagnostic accuracy of 95.65%. MSRSGC Category IVa was the most common, with 29 cases of pleomorphic adenoma. Conclusion: The overall diagnostic accuracy of cytological reporting of salivary gland lesions based on the Milan nomenclature in our institution was 95.65%. Our findings demonstrate the positive contribution of the MSRSGC towards accurately identifying malignant lesions, thereby assisting clinicians in making informed management decisions.